Papel do transportador ABC específico de Brucella ovis em sua sobrevivência intracelular e expressão de fatores de patogenicidade - Teane Milagres Augusto da Silva (2014)
Brucella ovis is a major cause of reproductive failure in rams and it is one of the few Brucella species that is not zoonotic. To verify how the ABC transporter plays a role during B. ovis in vitro and intracellular survival, the aims of this study were to compare proteomic profile and characterize intracellular trafficking of a mutant lacking a species-specific ABC transporter (abcAB). Proteomic analyses identified 55 protein spots differently expressed (p<0.05) between WT and abcAB strains, whereas 22 proteins showed lower expression in abcAB strain, including aminoacid and sugar ABC transporters, metabolic stress proteins, and Omp31. These results may illustrate potential roles of ABC transporter in B. ovis pathogenesis and intracellular survival. In HeLa cells, B. ovis WT was able to survive and replicate at later time point, whereas abcAB was attenuated at 24 hpi. In confocal analyses, mCherry-WT Brucella was able to avoid the LAMP-1+ compartment (~80%) at 48 hpi. However, almost 90% of mCherry-abcAB colocalized with LAMP-1+ compartment. Interestingly, abcAB mutant showed a weak expression of T4SS proteins (VirB8 and VirB11) in both rich and acid media, when compared to WT B. ovis. However, mRNA levels of virB1, virB8, hutC, and vjbR were similar in both strains. These results support the notion that ABC transporter is necessary for the expression of T4SS during late stages of B. ovis intracellular trafficking, although the transporter plays a role at a posttranscriptional level